A New Unified Intrusion Anomaly Detection in Identifying Unseen Web Attacks. (7th November 2017) - Kamarudin, Muhammad Hilmi; Maple, Carsten; Watson, Tim; Safa, Nader Sohrabi
Abstract : The global usage of more sophisticated web-based application systems is obviously growing very rapidly. Major usage includes the storing and transporting of sensitive data over the Internet. The growth has consequently opened up a serious need for more secured network and application security protection devices. Security experts normally equip their databases with a large number of signatures to help in the detection of known web-based threats. In reality, it is almost impossible to keep updating the database with the newly identified web vulnerabilities. As such, new attacks are invisible. This research presents a novel approach of Intrusion Detection System (IDS) in detecting unknown attacks on web servers using the Unified Intrusion Anomaly Detection (UIAD) approach. The unified approach consists of three components (preprocessing, statistical analysis, and classification). Initially, the process starts with the removal of irrelevant and redundant features using a novel hybrid feature selection method. Thereafter, the process continues with the application of a statistical approach to identifying traffic abnormality. We performed Relative Percentage Ratio (RPR) coupled with Euclidean Distance Analysis (EDA) and the Chebyshev Inequality Theorem (CIT) to calculate the normality score and generate a finest threshold. Finally, Logitboost (LB) is employed alongside Random Forest (RF) as a weak classifier, with the aim of minimising the final false alarm rate. The experiment has demonstrated that our approach has successfully identified unknown attacks with greater than a 95% detection rate and less than a 1% false alarm rate for both the DARPA 1999 and the ISCX 2012 datasets.